Scientific knowledge, innovation, and economic and social development - Silva, Elaine da [UNESP] (IGI Global, 2021)
Discussions about innovation in the organizational context were brought up between the mid 18th and 19th centuries; since then, concepts, definitions, and classifications of innovations have been created and incorporated into the academic and organizational contexts. The understanding of such concepts is fundamental for the agents involved to realize the different possibilities for the generation and management of innovation. This chapter, based on a literature review, develops a synthesis of concepts and classifications about innovation and presents a proposal for the analysis of innovative activity based on five dimensions: degree of novelty, object, focus, scope, and development. In addition, based on the assumption that universities are characterized as the most important producer of scientific knowledge in the context of innovation systems, it analyzes the modes of knowledge production and the respective role of scientific knowledge for the generation of innovation.